Ultrahigh frequency oscillations and multimode dynamics in vertical cavity surface emitting lasers - Leibenguth, R., author; Feld, S., author; Wilmsen, C., author; Rocca, Jorge J., author; Chilla, J. L. A., author; Buccafusca, O., author; American Institute of Physics, publisher (Colorado State University. Libraries, 1995)
We report the observation of ultrahigh frequency oscillations of up to 240 GHz in optically gain switched vertical cavity surface emitting lasers. These oscillations are shown to be produced by multimode emission through mode competition (10-30 GHz) or mode beating (above 100 GHz). Although these oscillations are not related to the intrinsic modulation bandwidth, some of them could be mistaken for relaxation oscillations, calling for careful interpretation of the results of this type of experiments. The highest frequencies observed for single mode relaxation oscillations were about 9 GHz in agreement with values of modulation bandwidth reported in the literature.